1999
DOI: 10.1046/j.1537-2995.1999.39199116893.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of blood‐derived stem and progenitor cells in normal subjects by granulocyte‐macrophage‐ and granulocyte‐colony‐stimulating factors

Abstract: BACKGROUND: It was previously reported that the combination of granulocyte‐macrophage‐colony‐stimulating factor (GM–CSF) and granulocyte‐CSF (G–CSF) for 4 days mobilized more primitive CD34+ subsets than did either G–CSF or GM–CSF alone. STUDY DESIGN AND METHODS: The studies determine the optimal number of days of growth factor dosing for mobilization and collection of peripheral blood progenitor cells, by increasing the days of administration of GM–CSF and/or G–CSF or employing the sequential administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…Our results, as well as those reported previously from other groups, demonstrate that GM-CSF used as a single agent is less effective than G-CSF for mobilization in normal donors. [16][17][18] Allografts mobilized by GM-CSF alone contained significantly fewer CD34 þ cells in comparison with G or G/GM and the donors required more LP procedures to obtain both the minimum and target CD34 þ cell doses. Further, several donors failed to reach a target of 5.0 Â 10 6 CD34 þ cells/kg and three of 31 (9.7%) mobilized less than 2.0 Â 10 6 CD34 þ cells/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, as well as those reported previously from other groups, demonstrate that GM-CSF used as a single agent is less effective than G-CSF for mobilization in normal donors. [16][17][18] Allografts mobilized by GM-CSF alone contained significantly fewer CD34 þ cells in comparison with G or G/GM and the donors required more LP procedures to obtain both the minimum and target CD34 þ cell doses. Further, several donors failed to reach a target of 5.0 Â 10 6 CD34 þ cells/kg and three of 31 (9.7%) mobilized less than 2.0 Â 10 6 CD34 þ cells/kg.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,17 Of note, several studies have demonstrated wide differences in the profile of monocytes, lymphocytes, and dendritic cells mobilized by the two agents. 14,16,[18][19][20] Since these graft constituents are likely to exert an influence on the development of GVHD and graft-versus-malignancy effects, we sought to determine the clinical impact of donor PBPC mobilization regimens using GM-CSF alone or in combination with G-CSF. In this retrospective analysis of uniformly treated and supported patients, we found that the transplantation of PBPC from HLA identical sibling donors mobilized with GM-CSF alone was associated with similar engraftment kinetics compared to G-CSF alone, but lower rates of moderate to severe acute GVHD.…”
Section: Csf; G-csfmentioning
confidence: 99%
“…23 The same consideration applies to the results of Spitzer et al, 24 who had somewhat different mobilization protocols. Closer to our procedure, To et al, 251 in 1994, showed that the CD34 + cell phenotype was different according to the mobilization protocols (CSF alone, or with chemotherapy) and Lane et al, 26 in 1999, showed that mobilization with the GM-CSF regimen gave more immature cells (CD34 + /CD38 − /HLA-DR + ). In our study, the level of progenitors obtained in peripheral blood for the patients receiving the combination of both CSFs was optimal on day 15.…”
Section: Discussionmentioning
confidence: 81%
“…1 As a result, it is now standard practice to administer disease-specific MC, followed by a colonystimulating factor, to facilitate neutrophil recovery, collect optimal numbers of CD34 + PBSCs, and more safely and effectively treat the associated malignancy. 1 Several studies suggest that the two most commonly used colony-stimulating factors in the United States, recombinant human granulocyte colony-stimulating factor (filgrastim) [2][3][4][5][6][7][8][9][10][11] and recombinant human granulocytemacrophage colony-stimulating factor (sargramostim), [12][13][14][15] yield high numbers of CD34 + cells in patients with good bone marrow reserves. Patients receiving these growth factors, especially filgrastim, experience quicker recovery of absolute neutrophil counts, less fever, and fewer hospital admissions, and receive fewer red blood cell transfusions and less i.v.…”
mentioning
confidence: 99%